Association of gag-myc proteins from avian myelocytomatosis virus wild-type and mutants with chromatin. - Bunte, T (1982)
The localization of the transformation-specific proteins was analyzed in quail embryo fibroblast cell lines transformed by wild-type avian myelocytomatosis virus MC29 and by three of its deletion mutants, Q10A , Q10C , and Q10H , with altered transforming capacities, and in a chicken fibroblast cell line transformed by the avian erythroblastosis virus (AEV). These viruses code for polyproteins consisting of part of the gag gene and of a transformation-specific region, myc for MC29 and erb A for AEV. Analysis by indirect immunofluorescence using monoclonal antibodies against p19, the N-terminal region of the polyprotein, showed that the gag-myc proteins in cells transformed by the wild-type MC29 as well as by the three deletion mutants are located in the nucleus. In contrast, cells transformed by AEV, which express the gag-erb A protein, give rise to cytoplasmic fluorescence. Fractionation of cells into nuclear and cytoplasmic fractions and analysis by immunoprecipitation and gel electrophoresis confirmed these results. About 60% of the gag-myc proteins of wild-type as well as of mutant origin were found in the nucleus, while 90% of the gag-erb A protein was present in the cytoplasm. Also, pulse-chase analysis indicated that the gag-myc protein rapidly accumulates in the nucleus in just 30 min. Further, it was shown that the wild-type and also mutant gag-myc proteins are associated with isolated chromatin. Association to chromatin was also observed for the gag-myc protein from MC29-transformed bone marrow cells, which are believed to be the target cells for MC29 virus in vivo.